Analisis Pengaruh Variabel Makro Ekonomi Dan Harga Komoditas Terhadap Jakarta Islamic Index (JII) - Ika Fitriyanti; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of this research is to determine the effects of macroeconomic variables to Jakarta Islamic Index in the period January 2013 – October 2015. The results of this research show that in partially world gold price (X1) does not have a significant influence to Jakarta Islamic Index (Y) which is indicated with t-test a significance value of 0.982. World oil price variable (X2) partially does not have a significant influence to Jakarta Islamic Index as evidenced by t test significant value of 0.090. Exchange Rate (X3) partially has a significant influence to Jakarta Islamic Index as evidenced by t test significant value of 0,003. Interest rate of Bank Indonesia (X4) has no significant influence to Jakarta Islamic Index as evidenced by t test significant value of 0.405. The result of all variables simultaneously have significant influence to Jakarta Islamic Index as evidenced by f test significant value of 0.03.